Hydroxychloroquine-Mediated Cardiotoxicity With a False-Positive 99mTechnetium–Labeled Pyrophosphate Scan for Transthyretin-Related Cardiac Amyloidosis. (January 2018) - Chang, Ian C.Y.; Bois, John P.; Bois, Melanie C.; Maleszewski, Joseph J.; Johnson, Geoffrey B.; Grogan, Martha
Abstract : Supplemental Digital Content is available in the text.